Training Needs to Develop Scientific Research Skills among the Coordinators of Talented Students in Light of the Standards of the National Olympiad for Scientific Creativity from Their Viewpoints - Khawaji, Mohammed Taher; Alhatheq, Abdulwahab Hassan Mohammed (Journal of Educational and Psychological Sciences, 2022)
This research aimed to determine the degree of importance of the training needs necessary to develop scientific research skills among coordinators of talented students according to the National Olympiad for Creativity standards from their points of view. In addition, the study aimed to identify the effect of gender, experience and degree variables on the degree of importance of those needs. To achieve such an aim, the descriptive survey method was used, and the research instruments included a questionnaire to determine the degree of importance of the training needs for the coordinators of talented students consisting of four main dimensions, which included (41) sub-needs. It was administered to a sample consisting of (120) of the research community, which amounted to (600) individuals at a rate of (20%). The research found that the degree of importance of training needs as a whole, and of the four sub-dimensions of the questionnaire (research needs, cognitive needs, and technical needs) attained a large degree, and the results indicated that there were no statistically significant differences at the level of (0.05) concerning the degree of importance of the training needs from the viewpoints of the research sample which might be attributed to the variables of gender, number of years of experience and academic qualification. The research also recommended developing training programs and courses with regard to scientific research skills for coordinators of the talented so that they stem from their needs, especially with regard to research, technical and knowledge needs, as well as intensifying training programs and courses for training coordinators of the talented students in public schools in the Kingdom of Saudi Arabia on scientific research skills.